MICROBIAL LACTIC ACID PRODUCTION: FIELD INSIGHTS AND FERMENTATION OPTIMIZATION (International Journal of Food and Nutritional Sciences, 2022)
The fermentative study focused on optimizing lactic acid production from cane sugar molasses using isolated Lactobacillus bacteria. The aim was to identify the most favorable conditions for high yield. Various process parameters including pH, temperature, inoculum size, incubation time, and agitation rate were optimized to maximize the conversion of cane sugar into lactic acid. The study determined that the ideal conditions for fermentation were a pH of 8.0, temperature of 40°C, and inoculum size of 7% (v/v), with an incubation time of 144 hours and agitation speed of 175 rpm. These optimized parameters offer potential for large-scale lactic acid fermentation using cane sugar as a substrate. The research underscores the significance of lactic acid as a valuable chemical derived from diverse sources, with cane sugar representing a viable option. Statistical analysis confirmed the significant impact of the optimized factors on lactic acid production. Future investigations could explore scaling up production using these parameters, thus advancing lactic acid fermentation practices.